Offline: The possible effects of Internet-related behavior on work values, expectations, & behavior among Ultra-Orthodox millennials. Issue 2 (4th March 2019) - Kay, Avi; Levine, Livia
ABSTRACT: This work examines differences in the work-related values, expectations, and behaviors between millennials who are significant users of technology and social media, and those who are not. We delineate the development of millennial behavior using a unique group of millennials, those in the Ultra-Orthodox Jewish (known as "Haredi") community in Israel. Due to religious and community norms, many Haredi millennials were shielded from digital technology, and particularly the Internet and the various technologies associated with it, such as text messaging and social media. Those who were raised and remained in Haredi communities did not encounter the Internet with any regularity as children. Many as adults are still unfamiliar with social media. Thus, this community presents a unique natural experiment, comparing Haredi millennials who are immersed in social media with those who are not.